A conceptual framework of blockchain-based portfolios to assess digital competence in WIL - Wanotayapitak, Sukosol (Asia-Pacific Journal of Science and Technology, 2021)
There appear to be three major problems when using ePortfolios to assess student competence with WIL (Work Integrated Learning) information systems, namely, the lack of information sharing, the lack of a link to the job market, and the lack of enhanced learning skills in the 21st century. This research aims to solve these problems by presenting a conceptual framework for blockchain-based portfolios to assess digital competence in WIL. The research methodology has four steps: step one – finding the situation and problems of using ePortfolios to assess competence in work-integrated learning (WIL), step two - analysing the causes and effects, step three - designing solutions, and step four - designing a conceptual framework.